PENGARUH EFIKASI DIRI TERHADAP PROKRASTINASI AKADEMIK PADA SISWA KELAS XI SMAN 1 TELUKJAMBE BARAT - Septiyan, Dwi; Simatupang, Marhisar; Sadijah, Nur Ainy (unprimdn.ac.id, 2023)
A school is a place where people learn. Students receive many assignments, especially those related to their subject. Educators give assignments to students to teach them to take advantage of their free time in understanding and are obliged to arrange the work given. However, in practice there are still problems related to the assignments given by the teacher. One of them is academic procrastination. Academic procrastination has several factors, one of which is low student self-efficacy. Therefore, this study aimed to determine the effect of self-efficacy on academic procrastination in class XI students of SMAN 1 Telukjambe Barat. This research uses quantitative methods. In this study, data collection used the self-efficacy scale which refers to Bandura's theory while academic procrastination refers to Ferrari's theory. This research involved 132 students as the research sample, selected from the total student population of 196 students using purposive sampling. The results of the simple linear regression analysis obtained sig. namely 0.000 <0.05 (p <0.05) which means that there is an effect of self-efficacy on academic procrastination seen from the value of count has a value of -5.132 meaning that if student self-efficacy is low then academic procrastination in these students will be high, besides that based on the results The calculation of the coefficient of determination shows that the magnitude of the influence of the self-efficacy variable on academic procrastination is 16.4%. In comparison, other variables influence the remaining 83.6%.